Analisis Pengaruh Rasio Keuangan Dan Sumber Pendanaan Internal Terhadap Potensi Terjadinya Financial Distress Pada Perusahaan Subsektor Otomotif Dan Komponen Yang Terdaftar Di Bursa Efek Indonesia Pada Periode 2018-2021 - Priyambudi, Arif; Susyanti, Jeni; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The decline in the automotive industry's performance since 2019 may have an impact on the risk of financial distress. This research aims to analyze the effect of financial ratios and internal funding sources on the potential of financial distress in automotive sub-sector and component companies listed on the Indonesian Stock Exchange. The dataused in this research is annual financial reports of automotive sub-sector and component companies listed on the Indonesian Stock Exchange for the period of 2018-2021. The method of analysis used is multiple linear regression analysis using SPSS 29.0. The results show that profitability, liquidity, activity, and internal funding sources has no effect on the potential of financial distress. Meanwhile, leverage ratio has a positive and significant effect on the potential of financial distress. Keywords: Financial Distress, Finantial Ratios, Internal Funding Sources, Automotive Sector Company